Percepción de los niños de primaria sobre la Educación Artística - Giuria Ulloa, Vanessa Claudia (2021)
The objective of this study was to explore the perceptions of elementary students about the art education they receive. For this reason, a qualitative approach of exploratory and descriptive character was used, as well as a phenomenological design where 12 children between 9 and 12 years of age were interviewed, who were attending primary education in regular basic schools in Lima. As part of the methodology, a semi-structured personal interview was used as the main information gathering strategy, along with two complementary activities solved by the children, that helped express their feelings in a more specific way. The study findings indicated that children can offer valuable information regarding their experiences at school with the art education they receive. Perceptions about art education were linked to the importance of these courses for their subjective well-being, their motivation, creativity, feelings of freedom, interpersonal relationships, identity and development of their skills and interests. Based on the findings, recommendations were made regarding the need to replicate the study in different educational contexts, as well as suggestions on what factors should be considered when implementing an appropriate arts education program.